Sleep health composites are associated with the risk of heart disease across sex and race - Lee, Soomi; Mu, Christina X; Wallace, Meredith L; Andel, Ross; Almeida, David M; Buxton, Orfeu M; Patel, Sanjay R (Scientific reports, 2022)
We examined whether subjectively and objectively measured sleep health composites have a relationship with heart disease. 6,820 adults (Mage = 53.4 years) from the Midlife in the United States study provided self-reported sleep characteristics and heart disease history. A smaller sample (n = 663) provided actigraphy sleep data. We tested two sleep health composites, based on self-report only and both self-report and actigraphy, across multiple sleep dimensions. We used a weighted sum approach, where higher scores indicated more sleep health problems. Modified Poisson regressions adjusted for sociodemographics and known risk factors. Having more sleep health problems was associated with a higher risk of heart disease using the self-report sleep health composite (aRR = 54%, P < .001) and the actigraphy/self-report composite (aRR = 141%, P < .001). Individual sleep dimensions of satisfaction, alertness, and efficiency (from the self-report composite) and regularity, satisfaction, and timing (from the actigraphy/self-report composite) were associated with the risk of heart disease. The effect size of each sleep health composite was larger than the individual sleep dimensions. Race moderated the association between the actigraphy/self-report sleep health composite and heart disease. There was no significant moderation by sex. Findings suggest poorer sleep health across multiple dimensions may contribute to heart disease risk among middle-aged adults.
Keywords: Surveys and Questionnaires; Sex Factors; poruchy iniciace a udržování spánku; Sleep Initiation and Maintenance Disorders; Humans; Risk; rasové skupiny; riziko; lidé středního věku; zpráva o sobě; Self Report; aktigrafie; nemoci srdce; Actigraphy; Female; dospělí; věkové faktory; lidé; sexuální faktory; průzkumy a dotazníky; Adult; ženské pohlaví; Male; spánková hygiena; Middle Aged; Racial Groups; Age Factors; mužské pohlaví; Sleep Hygiene; Heart Diseases